Austenite morphology and resistance to hydrogen embrittlement in medium Mn transformation-induced plasticity steel. (August 2019) - Jeong, Inkyun; Ryu, Kang Mook; Lee, Dae Geon; Jung, Yeonseung; Lee, Kyooyoung; Lee, Jae Sang; Suh, Dong-Woo
Abstract: Influence of austenite morphology on the hydrogen embrittlement in medium Mn transformation-induced plasticity (TRIP) steel was investigated. With nearly the same volume fraction and mechanical stability, the lath-type austenite is found to have more beneficial effect in relieving the hydrogen susceptibility compared to the equi-axed one. Slower hydrogen uptake and diffusion are confirmed in the steel with the austenite of lath-type morphology, which is possibly led by more connections between austenite grains obstructing the migration of hydrogen. Graphical abstract: Unlabelled Image